Structure, Function, and Benefits of Chloroplast DNA: Review Article - Akhmad Taufiq; Faustine Rahma Amelia; Zaskya Anjung Fortuna; Aulia Nyndita Wardani; Indraswari Ayu Camelia (Department of Biology Education FMIPA Universitas Negeri Yogyakarta in collaboration with Perhimpunan Biologi Indonesia, 2025)
Chloroplasts are double-membrane organelles that contain extranuclear DNA. The existence of this chloroplast genome (cpDNA) has an essential value for plant survival. This article will guide readers to comprehensively explore and answer questions about cpDNA, including the structure, function, mechanism expression, and inheritance, as well as the benefits of cpDNA. The method and analysis used are articles reviewed by searching, collecting, and analyzing related research articles. The main results obtained are the chloroplast genome in the form of a single quadripartite circular, its primary function for the synthesis of photosynthetic enzymes, and other functions as the biosynthesis of macromolecular compounds and secondary chloroplast metabolites, and plays a role in response to environmental stress, while the replication mechanism follows the maternal pattern in most Angiosperms and paternal in most Gymnosperms. The benefits of the chloroplast genome itself include the manufacture of recombinant pharmaceutical proteins, DNA barcoding, and Transplastomic. These results indicate that cpDNA has a crucial role in the survival of plants and humans. Further research and review regarding the relationship between environmental variables and the chloroplast genome are needed to complete the discussion on cpDNA.